Microshaping of aluminum-based neural microelectrode arrays using chemical wet-etching - Gonçalves, Sandra Beatriz Tomé (2014)
Chemical wet-etching is a standard technique for microelectrode arrays (MEA) fabrication. However its manufacturing reproducibility continues to be hindered by its dependence on several process parameters. Following previous works on aluminum-based MEA fabrication [1], this paper provides the first insight on a parametric study of the wet-etching process for an aluminum neural MEA. By playing around with some process parameters, one can achieve more homogeneous shafts with vertical or pyramidal profiles. High width uniformity (96%) along the high-aspect-ratio shafts was accomplished through the introduction of a sacrificial frame around the array. At the same time, the new fabrication approach transforms vertical square shafts into sharpened shafts with pyramidal geometries. Through fine control of the etching dynamics, different shafts geometries are feasible, allowing customized neural MEA designs for each application.